Resistance to anti-smoking messages related to the higher smoking stigma of Korean female smokers - Ha, Seung-Hyuk; Lee, Gi-Eun; Hwang, Jang-Sun; Lee, Jang-Han (Frontiers in Psychology, 2024)
Introduction The degree of perceived smoking stigma can differ, based on various factors such as gender; this may influence the effect of smoking cessation interventions, including denormalization. This study investigates the gender differences in smoking stigma recognized by Korean smokers and explores the effect of these differences on the success of smoking cessation messages that aim to initiate an identity crisis among smokers. It aims to contribute to effective smoking cessation intervention strategies for female smokers. Methods The smoker-gender Implicit Association Test (IAT) was used to measure gender-based smoking stigma; the test comprised photos of people smoking, with positive and negative descriptors. Participants were 120 smokers aged 19–35 years (60 males and 60 females). Participants’ cognitive attitudes toward smoking and cessation intentions were assessed at baseline. To investigate the effect of social stigmatization on smokers, participants were asked to watch anti-smoking campaigns that stigmatized either smoking behavior or smokers’ self-identity. Cognitive attitudes and cessations intention were used to show differences in gender and message conditions. Results The IAT D-score showed that female smokers perceived other female smokers significantly more negatively than they did male smokers, suggesting a higher level of smoking stigma. Female smokers in the socially stigmatizing condition reduced their negativity toward smoking less than those who were not stigmatized. Moreover, cessation intentions did not improve when female smokers received identity-threatening messages, indicating that female smokers tended to resist stigmatizing messages. Discussions These findings provide empirical evidence that the gender of Korean smokers is significantly related to differences in smoking stigma. The negative perception and resistance responses of female smokers shown in this study are consistent with the findings of previous studies on the stigma of substance use disorders and addiction. High smoking stigma can also be a risk factor in anti-smoking interventions, including health communication; therefore, these findings should be interpreted with caution.